Healthy lifestyle behaviours and its determinants in a sample of Portuguese adults - Pinto, Paula (2021)
Factors such as high adherence to the Mediterranean Dietary Pattern (MDP), physical activity (PA) and non-smoking, are associated with reduced mortality risk. This reduction is even more substantial when these healthy lifestyle factors are joined [1]. Thus, this study aimed at evaluating individual motivation to change lifestyle habits. An online questionnaire was designed and distributed among academic, institutional, and personal contacts between April and June 2020, with a total of 206 responses. Most of the participants were women (72,8%), with ages between 18 and 40 years old (79,1%), and resident on urban areas (94%). When inquired about if they would be willing to increase their well-being though adopting a healthier lifestyle, 83% answered yes, and 16% reported that they did not think about the subject. Most of the respondents reported that they would have benefits by changing three lifestyle behaviours: i) implement MDP habits (80%), mainly, increase consumption of water, vegetables and fruits, and decrease consumption of sugar; ii) increase practice of PA (70%), and iii) sleep seven to eight hours per night (45%). With respect to factos that would promote na increase in PA, most of the participants referred time as the main factor to include PA in the daily routine (61%). Other factors were the existence of appropriate places for PA practice near the residence (30%), the orientation of health professionals (16,5%), and the promotion of PA events in the area of residence (16%). In conclusion, food habits and PA were highlighted as the main factors influencing health and well-being of participants, with the lack of time as the most appointed factor for sedentarism. 1.Prinelli F, Yannakoulia M, Anastasiou CA, Adorni F, Di Santo SG, Musicco M, Scarmeas N, Correa Leite ML. Mediterranean diet and other lifestyle factors in relation to 20-year all-cause mortality: a cohort study in an Italian population. Br J Nutr. 2015 Mar 28;113(6):1003-11.